Answer: the above stated equation is a quadratic equation
Step-by-step explanation:
Given the following equations
y = x^2 + 5x - 3....equation 1
y-x = 2
y = x + 2........equation 2
Let equation 1 equal equation 2
x^2 + 5x -3 = x + 2
Bringing the equation to one side and equating to zero
X^2 +5x - 3 -x -2 = 0
X2 + 5x -x -3 -2 = 0
X^2 + 4x -5
Solving the aquatic equation
(x + 5)(x -1) = 0
X + 5 = 0
X1 = -5
X- 1 = 0
X2 = 1
To prove:
Substitute the values for x1and x2 into the equation x^2 + 4x - 5 = 0
the answer is .91 because you have to move the decimal two places to the left
Answer:
-4
Step-by-step explanation:
Brainliest please?
Answer:
its 5 m/minute
Step-by-step explanation:
you have to use the units that are given in the equation
pls mark brainliest if you geel like it...
The account balance after 3 years if the interest is compounded continuously is $5,142.62
<h3>How to find compound interest?</h3>
- Principal, P = $4,700
- Time,t = 3 years
- Interest rate, r = 3%
r = 3/100
r = 0.03 rate per year,
A = Pe^rt
A = 4,700.00(2.71828)^(0.03)(3)
= 12,775.916^0.09
A = $5,142.62
Therefore, the account balance after 3 years if the interest is compounded continuously is $5,142.62
Learn more about compound interest:
brainly.com/question/24924853
#SPJ1